An investigation of tourists' destination image, satisfaction and destination loyalty: Batu Ferringghi Beach, Penang - Goo, Y.M; Yew, X.T.; See, S.F. (2014)
This study compares local and international tourists regarding to their perception towards destination image, overall satisfaction and destination loyalty with their visit(s) to Batu Ferringhi Beach, Penang.This research was also conducted to examine the relationship between destination images, tourist satisfaction and destination loyalty towards Batu Ferringghi.The data were collected from 254 local and international tourists at Batu Ferringhi Beach from August to September 2013 by using convenience sampling technique.Local and international tourists differed in their views of Batu Ferringghi in the aspect of safety, cleanliness, scenic and tourists‘ satisfaction.Both groups would revisit Batu Ferringghi and recommend Batu Ferringhito others.Regression analysis revealed that three destination image including safety, cleanliness and scenic has a direct effect on tourists‘ satisfaction and destination loyalty and tourists‘ satisfaction has a direct effect on destination loyalty.